2016
DOI: 10.1152/jn.00452.2015
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of motor unit firings: an epiphenomenon of firing rate characteristics not common inputs

Abstract: Kline JC, De Luca CJ. Synchronization of motor unit firings: an epiphenomenon of firing rate characteristics not common inputs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 86 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…Supporting this notion, previous studies (Milner‐Brown et al., ; Semmler & Nordstrom, ; Semmler, ; Folland & Williams, ) have reported increased MU synchronization in strength athletes compared to endurance athletes or untrained individuals, which has been accompanied by similar observations for RFD (Kyrolainen & Komi, ; Paasuke et al., ; Andersen et al., ). However, in spite of its apparent wide acceptance, there is a lack of empirical evidence supporting the notion that increased common synaptic inputs to spinal motor neurons result in enhanced MU synchronization under voluntary conditions (Kline & De Luca, ). In fact, a recent study (Kline & De Luca, ) concluded that as the force generated by the muscle increases, the firing rate slope decreases and the synchronization consequently decreases.…”
Section: Physiological Factors That Can Affect Rate Of Force Developmentmentioning
confidence: 99%
“…Supporting this notion, previous studies (Milner‐Brown et al., ; Semmler & Nordstrom, ; Semmler, ; Folland & Williams, ) have reported increased MU synchronization in strength athletes compared to endurance athletes or untrained individuals, which has been accompanied by similar observations for RFD (Kyrolainen & Komi, ; Paasuke et al., ; Andersen et al., ). However, in spite of its apparent wide acceptance, there is a lack of empirical evidence supporting the notion that increased common synaptic inputs to spinal motor neurons result in enhanced MU synchronization under voluntary conditions (Kline & De Luca, ). In fact, a recent study (Kline & De Luca, ) concluded that as the force generated by the muscle increases, the firing rate slope decreases and the synchronization consequently decreases.…”
Section: Physiological Factors That Can Affect Rate Of Force Developmentmentioning
confidence: 99%
“…Recently the existence of common input has been debated: while some argue that synergistic muscles share most of their synaptic input (Laine et al, 2015 ), others have argued that common input provides no explanation for MN synchronization (Kline and De Luca, 2016 ). Apart from common input being used to explain different types of MN synchronization, this dispute mainly arises from the absence of a clear definition of common input (cf.…”
mentioning
confidence: 99%
“…The first one is short-term synchronization (STS) that occurs within short time period (around 5 ms) as reflected with a narrow peak in the cross-correlogram (Kirkwood et al, 1982 ). The STS may either arise from the common axonal inputs to pairs of motoneurones (Sears and Stagg, 1976 ; Nordstrom et al, 1992 ) or be just an epiphenomenon of firing rate characteristics (Kline and de Luca, 2016 ). The other form of synchronization is long-term (or broad-peak) one (LTS) that occurs within broader time band (>20 ms) (Kirkwood et al, 1982 ; Freund, 1983 ).…”
Section: Discussionmentioning
confidence: 99%